Interdisciplinarity in tech startups development: Case study of "unistartapp" project - Sebastian Kopera; Ewa Wszendybył-Skulska; Joanna Cebulak; Sebastian Grabowski (Foundations of Management, 2018)
Empirical data as well as scientific reports confirm that startups require diverse, in-house competencies in order to achieve market success. However, while technology-related competencies are usually brought to new tech ventures by their founders, there is a significant deficiency of market- and management-related competencies, which is reflected in the statistics of common startup failure reasons. In this context, a question arises: how interdisciplinarity of knowledge and competencies can be built into the very core of tech startups? The text addresses this question by zeroing in on the role of universities in this process. In the first part, the specificity of tech startups is analyzed. The next chapter overviews the hitherto academy-related startup education environment together with its shortcomings as far as interdisciplinarity is concerned. Finally, the case study of innovative and interdisciplinary academic ecosystem, which was built and tested within the project UniStartApp, is presented and discussed together with related lessons learned. The text is concluded with final remarks on challenges involved in embedding interdisciplinarity into startup education ecosystem.
Keywords: 650; startup education; entrepreneurship; tech startups; education ecosystem; formal education; academic entrepreneurship; competencies; knowledge